2019
DOI: 10.1097/fjc.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caspase 1 in Ischemia/Reperfusion Injury of the Myocardium

Abstract: Acute occlusion of a coronary artery can result in myocardial infarction-a leading cause of premature death. Prompt restoration of blood flow to the myocardium can prevent excessive death of cardiomyocytes and improve clinical outcome. Although the major mechanism of cell death after reperfusion is necrosis, it is now recognized that many other cell death pathways may be involved in ischemia-reperfusion (I/R) injury. Pyroptosis is one such cell death pathway that is caspase-1-dependent and induced in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 66 publications
(99 reference statements)
0
30
0
Order By: Relevance
“…101,102 Conversely, it also reported that caspase-1 can directly initiate inflammatory-induced cell death through the activation of the gasdermin-D-induced pyroptosis pathway, which in turn results in cardiomyocyte death, excessive scar formation, and poor ventricular remodeling. 103 Other experimental studies on mice also reported that activation of NLRP3 inflammasome and caspase-1 may cause excessive cell death in cardiac ischemia. Thus, they suggested that inhibition of caspase-1 activation may have a great role in the progression of cardiac ischemia due to excessive cell death.…”
Section: Role Of Caspase-1 In Cardiovascular Diseasesmentioning
confidence: 98%
See 1 more Smart Citation
“…101,102 Conversely, it also reported that caspase-1 can directly initiate inflammatory-induced cell death through the activation of the gasdermin-D-induced pyroptosis pathway, which in turn results in cardiomyocyte death, excessive scar formation, and poor ventricular remodeling. 103 Other experimental studies on mice also reported that activation of NLRP3 inflammasome and caspase-1 may cause excessive cell death in cardiac ischemia. Thus, they suggested that inhibition of caspase-1 activation may have a great role in the progression of cardiac ischemia due to excessive cell death.…”
Section: Role Of Caspase-1 In Cardiovascular Diseasesmentioning
confidence: 98%
“…Surprisingly, in fibroblast cells, caspase-1 involves the maturation of IL-1β-mediated myofibroblast differentiation and collagen synthesis. 103,[116][117][118] In animals, fibroblasts are the most common cells of connective tissue that produce the structural framework of the tissue through the synthesis of extracellular matrix and collagen. Fibroblasts can also be involved in the inflammatory responses for tissue injuries or infections through the induction of chemokine synthesis.…”
Section: Role Of Caspase-1 In Cardiovascular Diseasesmentioning
confidence: 99%
“…Interaction of these proteins with cellular pattern recognition receptors can lead to the assembly of the intracellular NLRP3 inflammasome complex. The assembled NLRP3 inflammasome elicits auto‐proteolytic cleavage and activation of caspase‐1, which mediates the cleavage/maturation of the pro‐inflammatory cytokines, pro‐IL‐18 and pro‐IL‐1β, and cleaves/activates gasdermin‐D (GSDMD), releasing its N‐terminal fragment . Activated GSDMD‐N, as well as active caspase‐1, may induce the formation of membrane pores thus inducing cell lysis, called pyroptotic cell death .…”
Section: Pyroptosismentioning
confidence: 99%
“…In mice and rats with permanent coronary ligation, a marked increase in NLRP3, IL-1β, and IL-18 mRNA expression was found in the LV from 3 to 21 days after CAO, primarily located in myocardial fibroblasts [106]. Caspase-1 activity is increased in the myocardium minutes after the onset of ischaemia and remains elevated for several days, leading to cardiomyocyte death and amplification of inflammation [100]. Mice lacking caspase-1 that were subject to CAO exhibited both improved peri-infarct survival and a decreased rate of ventricular dilatation, presumably due in part to a decrease in MMP-3 activity, IL-18 production, and a reduction in the rate of apoptosis [34].…”
Section: Ventricular Remodellingmentioning
confidence: 99%